Metaphor and Contextual Meaning in Selected Songs of Charlie Puth’s Album Nine Track Mind - Daffa Praditya Devano; Sayyid Khairunas (Journal of Applied Linguistics, 2026)
This research aims to investigate the use of metaphor and contextual meaning in selected songs from Charlie Puth’s album Nine Track Mind. The study draws upon figurative language theory and contextual semantics as the main analytical frameworks. The objective is to find metaphor within the songs, contextual meaning from the songs, and the overall message of the album. Using a qualitative descriptive method, the study focuses on five songs: “One Call Away,” “Dangerously,” “Marvin Gaye,” “We Don’t Talk Anymore,” and “See You Again.” A total of 28 metaphorical expressions were identified, each reflecting emotions such as longing, heartbreak, desire, and personal growth. Contextual meaning was also analyzed to uncover how social, emotional, and cultural backgrounds shape lyric interpretation. The findings show that metaphors in Puth’s lyrics effectively convey emotional depth and connect with listeners’ experiences. Contextual elements add further meaning, enriching the interpretation of the songs. The album as a whole communicates themes of vulnerability, emotional struggle, and modern relationship dynamics. This study concludes that metaphor and context together create multi-layered meanings in song lyrics and offer valuable insights into semantic expression through music. Keywords : Metaphors; Contextual Meaning; Semantics;, Song Lyrics